Nerve Enlargement in Patients with INF2 Variants Causing Peripheral Neuropathy and Focal Segmental Glomerulosclerosis - Quynh Tran Thuy Huong; Linh Tran Nguyen Truc; Hiroko Ueda; Kenji Fukui; Koichiro Higasa; Yoshinori Sato; Shinichi Takeda; Motoshi Hattori; Hiroyasu Tsukaguchi (Biomedicines)
Background: Charcot–Marie–Tooth (CMT) disease is an inherited peripheral neuropathy primarily involving motor and sensory neurons. Mutations in INF2, an actin assembly factor, cause two diseases: peripheral neuropathy CMT-DIE (MIM614455) and/or focal segmental glomerulosclerosis (FSGS). These two phenotypes arise from the progressive degeneration affecting podocytes and Schwann cells. In general, nerve enlargement has been reported in 25% of the demyelinating CMT subtype (CMT1), while little is known about the CMT-DIE caused by INF2 variants. Methods: To characterize the peripheral nerve phenotype of INF2-related CMT, we studied the clinical course, imaging, histology, and germline genetic variants in two unrelated CMT-DIE patients. Results: Patient 1 (INF2 p.Gly73Asp) and patient 2 (p.Val108Asp) first noticed walking difficulties at 10 to 12 years old. Both of them were electrophysiologically diagnosed with demyelinating neuropathy. In patient 2, the sural nerve biopsy revealed an onion bulb formation. Both patients developed nephrotic syndrome almost simultaneously with CMT and progressed into renal failure at the age of 16 to 17 years. Around the age of 30 years, both patients manifested multiple hypertrophy of the trunk, plexus, and root in the cervical, brachial, lumbosacral nerves, and cauda equina. The histology of the cervical mass in patient 2 revealed Schwannoma. Exome analysis showed that patient 2 harbors a germline LZTR1 p.Arg68Gly variant, while patient 1 has no schwannomatosis-related mutations. Conclusions: Peripheral neuropathy caused by INF2 variants may lead to the development of multifocal hypertrophy with age, likely due to the initial demyelination and subsequent Schwann cell proliferation. Schwannoma could co-occur when the tissues attain additional hits in schwannomatosis-related genes (e.g., LZTR1).